Infestation by potato tuber moth restructures microbial communities in flue-cured tobacco rhizosphere and non-rhizosphere soils - Sun, Ganlin; Li, Zhi; Wang, Guang; Cai, Haosheng; Yu, Junkun; Li, Zhengbin; Chen, Bin; Xiao, Guanli (Frontiers in Plant Science, 2025)
IntroductionThe rhizosphere microbiota is associated with the plant response to phytophagous pest infestation through the plant-rhizosphere microbe axis. However, the responses of microbial community characteristics of flue-cured tobacco rhizosphere and non-rhizosphere soil to potato tuber moth (PTM) Phthorimaea operculella larval feeding is unclear.MethodsIn this study, the microbial structural composition was analysed in the rhizosphere and non-rhizosphere soil of healthy and PTM infested flue-cured tobacco plants at the vigorous growth stage collected from the field (with four replicates per group) using Illumina MiSeq sequencing. The featured microbes, co-occurrence networks, and potential functions of tobacco rhizosphere and non-rhizosphere soil microbial communities were analysed.ResultsAmplicon data analyses showed that PTM infestation altered the microbial community composition in tobacco rhizosphere and non-rhizosphere and this alteration was similar between these two soil types. PTM infested plants showed enrichment of distinct microbial genera. For instance, the rhizosphere soil showed increased abundances of Gemmatimonas (bacteria) and Humicola (fungi), while the non-rhizosphere soil was enriched with Streptomyces (bacteria) and Penicillium (fungi). In contrast, the rhizosphere of healthy plants were characterized by enrichment of Gaiella (bacteria) and Trichoderma, Talaromyces (fungi), along with the non-rhizosphere soil dominated by Sphingomonas (bacteria) and Cordana (fungi). Furthermore, PTM infestation altered the potential functions of flue-cured tobacco rhizosphere and non-rhizosphere soils, and reduced the complexity of rhizosphere bacterial and fungal communities, as well as the non-rhizosphere fungal community. Notable changes were observed in bacterial metabolic pathways and significantly up-regulated the function of symbiotroph of fungi (Lichenized) (P < 0.05).DiscussionTogether, these results enhance our understanding of how the underground microbiome of flue-cured tobacco responds to aboveground phytophagous insect (PTM) infestation, providing valuable insights that could facilitate translation into more effective PTM management practices.